First Aerial South Atlantic Night Crossing - Neves, Fernando M. S. P. (2022)
The history of the transatlantic flights began in 1919 when Albert C. Read’s team flew between Newfoundland and Lisbon, with a stopover at Azores, for fuel and repairs. The flight was made following a chain of 60 U.S. warships in order to guide it along its route and to provide assistance if needed. Two weeks later, John Alcock and Sir Arthur Whitten Brown made the first nonstop transatlantic flight from Newfoundland to County Galway, Ireland, covering more than 3000 km in just 16 hours of flight. In 1922, Gago Coutinho and Sacadura Cabral crossed the South Atlantic Ocean by air, for the first time using only internal means of navigation: a modified sextant and a course corrector; both devices proved its effectiveness. The Portuguese Aeronautics rejoiced auspicious days that time, with its aviation pioneers trying consecutively to reach more distant places along intercontinental flights. Several Around-the-World Flight Attempts were made in 1924: United States, England, France, Portugal, Argentina and Italy. However the circumnavigation purpose was only officially confirmed before the general public, when a considerable flying progress was achieved. In 1923, Gago Coutinho and Sacadura Cabral were contemplating to perform an Around the World Flight, a dream pursued also by Sarmento de Beires in 1924 and 1927. In 1927 and by following the knowledge obtained by Coutinho and Cabral, four Portuguese Airmen started an Around the World Flight Attempt in a mission that ended with seaplane sunk at the Ocean; however this mission was renamed after the seaplane loss and became known in the World as the First Aerial South Atlantic Night Crossing. For the first time in history, during the night of 16 to 17 March 1927, a Portuguese crew flew 2595 km over the Atlantic Ocean from Guinea, Africa to Fernando de Noronha Island, Brazil. The flight was made only by astronomical processes navigation resources that proved again to be absolutely feasible and trustworthy, regardless day or night lighting conditions.